Validation of the instrument to measure the level of knowledge of postgraduate and university professors on the labor law of the dental surgeon - Zapata Sifuentes, Mauricio A. (2022)
Objective: To build and validate an instrument to measure the level of knowledge about the Law that regulates the work of the dental surgeon in the Peruvian territory (Law No. 27878) of postgraduate students and teachers of the Stomatology Career of the Scientific University of South. Peru. Material and methods: The sample consisted of 38 dental surgeons, participants in the postgraduate program (20) and professors (18) of the Stomatology Career at the Universidad Científica del Sur. A structured questionnaire of 15 questions was developed based on the articles of Law No. 27878. Results: It was approved by Expert Judgment and submitted to Aiken's V with an average result of 0.95. A moderate level of correlation was obtained through the Pearson Correlation Coefficient and a Cronbach's Alpha of 0.8. Through the Exploratory Factor Analysis, 3 dimensions were formed. Conclusions: The instrument was correctly validated through 4 validity　tests. The level of knowledge of postgraduate students and teachers was very good in 60.5%.